Impact of climate change and variability on the production and composition of dairy cow milk in the central part of Ethiopia - Teshome Gemechu; Mitiku Eshetu; Yesihak Yusuf Mummed; Ulfina Galmessa; Aemiro Kehaliew (Food Chemistry Advances)
The study aimed to assess the impact of climate change and variability on dairy cows' milk composition and production. A factorial analysis of variance was performed on all milk composition characteristics to evaluate whether the seasonal variation was significant. Raw milk sample analysis revealed that milk compositions were highest during the wet season and lowest during the dry season (p < 0.05). Throughout the study period, milk fat was positively correlated (p < 0.001) with lactose, protein, SNF, ash, and RH. Conversely, a negative correlation was observed between the mean temperature and milk fat, lactose, protein, SNF, and ash throughout the seasons. From the study, it was concluded that the maximum THI during the dry season in the Ada'a Berga dairy farm was within the range of moderate heat stress. These results indicate that actions should be taken to prevent heat stress in dairy cows during the dry season.